Effect of T-junction diameter ratio on stratified-wavy flow separation - Saieed, A. (Elsevier B.V., 2018)
Most of the research carried out on reduced diameter ratio T-junctions concluded that partial phase separation can be improved by decreasing the diameter ratio. Despite using very small diameter ratio T-junctions, petroleum industry has always faced the problem of continuous and sometimes very high liquid carryovers. In this regard, the separation of air-water stratified-wavy flow in 1.0, 0.52, 0.67, 0.27 and 0.20 diameter ratio T-junctions was examined to investigate the effect of diameter ratio on phase separation. Phase distribution of each T-junction was evaluated by observing the point at which liquid carryover starts (liquid carryover threshold) and the maximum liquid carryover delivered (peak liquid carryover). For optimum separation it is essential that liquid carryover threshold is high and peak liquid carryover is low, however these parameters were found to decrease with the reduction in diameter ratio. It was observed that in stratified-wavy flow, the drop in liquid carryover threshold was reasonable and thus in this flow regime a decrease in diameter ratio was always found to enhance phase separation. Two correlations were also developed to predict the phase splitting behavior, under a wide range of operating conditions. Â© 2018 Elsevier B.V.